METHODS OF QUANTITATIVE DETERMINATION OF "PHENIGAMMA" ELABORATION USING UV SPECTROPHOTOMETRY - B. V. Borovskiy; D. D. Shabardina (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
We have elaborated a methodology for quantitative determination of new biologically active derivative of GABA using UV spectrophotometry. The results obtained allowed us recommending this methodology for use in pharmaceutical analysis as excipient, and as drug dosage for quantitative analysis